La ética en el arte de cuidar (2002)
ABSTRACT: The article works nursing care as the ultimate and the essence of the nursing profession. It considers the professional nurse as care given care itself -the others and the environment in relation to the subject of care- individual, families and collectives- It states the principles of ethics and moral virtues as ethical components of caring and concludes with some very precise recommendations for nursing care of excellent quality.